A Behavioral Economics Perspective on Tobacco Taxation - Cherukupalli, Rajeev (American Public Health Association, 2010)
Economic studies of taxation typically estimate external costs of tobacco use to be low and refrain from recommending large tobacco taxes. Behavioral economics suggests that a rational decision-making process by individuals fully aware of tobacco's hazards might still lead to overconsumption through the psychological tendency to favor immediate gratification over future harm. Taxes can serve as a self-control device to help reduce tobacco use and enable successful quit attempts. Whether taxes are appropriately high depends on how excessively people underrate the harm from tobacco use and varies with a country's circumstances. Such taxes are likely to be more equitable for poorer subgroups than traditional economic analysis suggests, which would strengthen the case for increased tobacco taxation globally.